A new, potential and safe neoadjuvant therapy strategy in epidermal growth factor receptor mutation-positive resectable non-small-cell lung cancer-targeted therapy: a retrospective study - Liu, Baoxing; Liu, Xingyu; Xing, Huifang; Ma, Haibo; Lv, Zhenyu; Zheng, Yan; Xing, Wenqun (Frontiers in Oncology, 2024)
Background Studies of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in resectable non-small-cell lung cancer (NSCLC) have been conducted. The purpose of our study was to evaluate the benefits of osimertinib as neoadjuvant therapy for resectable EGFR-mutated NSCLC. Method This retrospective study evaluated patients with EGFR mutations in exon 19 or 21 who received targeted therapy with osimertinib (80 mg per day) before surgery between January 2019 and October 2023 in Henan Cancer Hospital. Results Twenty patients were evaluated, all of whom underwent surgery. The rate of R0 resection was 100% (20/20). The objective response rate was 80% (16/20), and the disease control rate was 95% (19/20). Postoperative pathological analysis showed a 25% (5/20) major pathological response rate and 15% (3/20) pathological complete response rate. In total, 25% (5/20) developed adverse events (AEs), and the rate of grades 3–4 AEs was 10% (2/20). One patient experienced a grade 3 skin rash, and 1 patient experienced grade 3 diarrhea. Conclusion Osimertinib as neoadjuvant therapy for resectable EGFR-mutated NSCLC is safe and well tolerated. Osimertinib has the potential to improve the radical resection rate and prognosis.